Vaccination against hepatitis A virus may not be required for schoolchildren in northern India: results of a seroepidemiological survey - Batra Yogesh; Bhatkal Bharati; Ojha Bandana; Kaur Kuldeep; Saraya Anoop; Panda Subrat Kumar; Acharya Subrat Kumar (The World Health Organization, 2002)
OBJECTIVES: To evaluate the current seroprevalence of antibodies against hepatitis A virus (HAV) in a sample of schoolchildren above 10 years of age and to determine the prevalence of HAV-induced hepatitis in adults at a tertiary care hospital in northern India between January 1992 and December 2000. METHODS: Sera from 276 male and 224 female schoolchildren aged 10-17 years were tested for anti-HAV antibodies by enzyme-linked immunosorbent assay. Consecutive patients with a diagnosis of acute viral hepatitis who attended a liver clinic were tested for the serological markers of HAV, hepatitis B Virus, hepatitis C virus, hepatitis D virus, and hepatitis E virus. FINDINGS: Of the male and female children, 96.3% and 98.2%, respectively had anti-HAV antibodies in their sera. The prevalence of these antibodies in the age groups 10-12, 13- 14, and 15-17 years were 98.6%, 94.8%, and 98.3% respectively. The frequency of HAV- induced acute viral hepatitis (69/870, 8%) in adults did not show an increasing trend. CONCLUSION: Mass HAV vaccination may be unnecessary in northern India because the seroprevalence of protective antibodies against HAV in schoolchildren aged over 10 years remains above 95% and there has been no apparent increase in HAV-induced acute viral hepatitis in adults.